Solitary Wave Solutions for Zoomeron Equation - IRSHAD, Amna; MOHYUD-DIN, Syed Tauseef (Walailak Journal of Science and Technology (WJST), 2012)
Tanh-Coth Method is applied to find solitary wave solutions of the Zoomeron equation which is of extreme importance in mathematical physics. The proposed scheme is fully compatible with the complexity of the problem and is highly efficient. Moreover, suggested combination is capable to handle nonlinear problems of versatile physical nature.